Treatment of HIV-1 Infection with Combination Therapy: Antiretroviral Agents and Biological Response Modifiers - Steven M Schnittman (Canadian Journal of Infectious Diseases)
While nucleoside antiretroviral agents are effective in delaying disease progression in human immunodeficiency virus (HIV - infected individuals. their activity is limited in magnitude and duration. Therefore, approaches to attacking HIV via combination therapies have recently been under investigation. In particular, since HIV infection dysregulates and destroys the immune system. it is logical to develop therapeutic approaches that would both restore the immune response and have direct antiviral activity. Preliminary evaluations of the combination of zidovudine wilh interferon alpha (IFN-α) have demonstrated enhanced antiviral. antitumour and immunomodulatory activity. Other promising approaches include antiretroviral therapy with interleukin (IL) -2, and IFN-α wilh IL-2. The clinical research pertaining to these combinations of antiretrovirals and biological response modifiers is reviewed.